2010
DOI: 10.1016/j.stem.2010.02.014
|View full text |Cite
|
Sign up to set email alerts
|

An Oct4-Centered Protein Interaction Network in Embryonic Stem Cells

Abstract: SummaryTranscription factors, such as Oct4, are critical for establishing and maintaining pluripotent cell identity. Whereas the genomic locations of several pluripotency transcription factors have been reported, the spectrum of their interaction partners is underexplored. Here, we use an improved affinity protocol to purify Oct4-interacting proteins from mouse embryonic stem cells (ESCs). Subsequent purification of Oct4 partners Sall4, Tcfcp2l1, Dax1, and Esrrb resulted in an Oct4 interactome of 166 proteins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
479
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 499 publications
(517 citation statements)
references
References 57 publications
(68 reference statements)
30
479
5
Order By: Relevance
“…This has been interpreted as reflecting participation of Oct4 in diverse transcription factor complexes that differentially regulate gene expression and may contribute either to maintenance of pluripotency or to lineage specification (Niwa et al 2000). Protein interaction studies are consistent with the expectation that Oct4 has multiple partners (Pardo et al 2010;van den Berg et al 2010). …”
Section: A Transcription Factor Network That Sustains Naïve Pluripotencysupporting
confidence: 59%
“…This has been interpreted as reflecting participation of Oct4 in diverse transcription factor complexes that differentially regulate gene expression and may contribute either to maintenance of pluripotency or to lineage specification (Niwa et al 2000). Protein interaction studies are consistent with the expectation that Oct4 has multiple partners (Pardo et al 2010;van den Berg et al 2010). …”
Section: A Transcription Factor Network That Sustains Naïve Pluripotencysupporting
confidence: 59%
“…These observations are interesting given the role of an ES cell form of BAF in maintaining pluripotency [99][100][101] and the detection of Brg1 and Baf155 in Oct4 protein complexes [76]. This may suggest that BAF acts by facilitating chromatin binding of Oct4 to promoters during factor-directed reprogramming.…”
Section: Molecular Mechanisms Of Reprogramming In Other Model Systemsmentioning
confidence: 89%
“…In addition, protein interaction analyses are revealing associations between critical protein components in the network [74][75][76][77]. While all the above studies are important for generating hypotheses, many of the measurements have the limitation that they are snapshots of a fixed moment and thus operate as population averages, ignoring potentially functional variation within apparently homogeneous cell populations.…”
Section: Mechanisms That Underpin Pluripotencymentioning
confidence: 99%
“…Recent proteomic screens, taking a more unbiased approach, have expanded these networks considerably by screening for proteins that directly interact with pluripotency factors. This has indicated that Oct4 (Pardo et al 2010;van den Berg et al 2010) and Nanog (Wang et al 2006), either directly or indirectly, interact with an extensive set of proteins, including transcription factors, chromatin remodelers, and components of the basal transcriptional machinery. Many of these interactions have been shown to be functional, indicating that the activity of both Oct4 and Nanog is modulated by a large number of cofactors (Wang et al 2006;Pardo et al 2010;van den Berg et al 2010).…”
Section: Protein-protein Interactionsmentioning
confidence: 99%
“…This has indicated that Oct4 (Pardo et al 2010;van den Berg et al 2010) and Nanog (Wang et al 2006), either directly or indirectly, interact with an extensive set of proteins, including transcription factors, chromatin remodelers, and components of the basal transcriptional machinery. Many of these interactions have been shown to be functional, indicating that the activity of both Oct4 and Nanog is modulated by a large number of cofactors (Wang et al 2006;Pardo et al 2010;van den Berg et al 2010). This notion also emerged from an elegant study, where affinity purification and lentiviral expression were combined to identify interactions between transcription factors and chromatin remodeling complexes (Mak et al 2010).…”
Section: Protein-protein Interactionsmentioning
confidence: 99%